Pengaruh Aktivitas Manusia terhadap Beban Pencemaran Sub DAS Sungai Rengas, Kalimantan Barat (The Influence of Human Activities on Pollution Load on The Rengas River Sub Water, West Kalimantan) - Lusiyana Lusiyana; Aji Ali Akbar; Herda Desmaiani (Universitas Tanjungpura, 2021)
Abstract This study aims to knowing the potential pollutant loads entering and to know how water quality Rengas River according to water quality standard Class II Per-Men No. 82, 2001. Water quality analysis was carried out by testing and comparing parameters of temperature, pH, DO, BOD, TSS and phosphate at high tide and low tide conditions. The determination of the status of water quality using the Pollution Index method. The results of the pollution index show that the condition of the Rengas River is categorized as lightly polluted and concentration of TSS and BOD exceeded the class II quality standard at low tide During high tide conditions, the highest IP value is at point 1 of 1.29 in the upstream part of the river, while the lowest IP value is at point 4 of 0.71. During low tide, the largest IP value is at point 1 of 1.5 which is located upstream of the river, while the lowest IP value is at point 5 of 1.08 where there is tofu processing. Based on the identification and inventory of the sources of pollution affecting the water quality of Sungai Rengas from the agricultural sector, the domestic sector and small-scale industrial sector. The pollutant load that enters the Rengas River is TSS of 21 . 666.49 kg / day , BOD of 15053.68 kg / day , and phosphates of 85.56 kg / day . The largest BOD and TSS pollutant loads come from segment 3, which in this segment includes high density residential land uses and commercial land uses. Keywords: Rengas River, Pollutants Load, Water Quality Status Abstrak Penelitian ini bertujuan untuk mengetahui potensi beban pencemar yang masuk dan kualitas air Sungai Rengas menurut baku mutu kualitas air Kelas II Per-Men No. 82 Tahun 2001. Analisis kualitas air dilakukan dengan menguji dan membandingkan parameter suhu, pH, DO, BOD, TSS dan fosfat pada kondisi pasang dan surut. Penentuan status mutu air menggunakan metode Indeks Pencemaran. Nilai indeks pencemaran menunjukkan bahwa kondisi Sungai Rengas masuk ke dalam kategori tercemar ringan dan konsentrasi TSS dan BOD melebihi baku mutu kelas II saat surut. Saat kondisi pasang nilai IP tertinggi ada pada titik 1 sebesar 1,29 di bagian hulu sungai, sedangkan nilai IP terendah ada pada titik 4 sebesar 0,71. Saat kondisi surut nilai IP terbesar ada pada titik 1 sebesar 1,5 yang terletak pada hulu sungai, sedangkan nilai IP terendah ada pada titik 5 sebesar 1,08 dimana terdapat pengolahan tahu. Berdasarkan identifikasi dan inventarisasi sumber pencemar yang mempengaruhi kualitas air Sungai Rengas berasal sektor pertanian, sektor domestik dan sektor industri skala kecil. Beban pencemar yang masuk ke Sungai Rengas yaitu TSS sebesar 21.666,49 kg/hari, BOD sebesar 15.053,68 kg/hari, dan Fosfat sebesar 85,56 kg/hari. Beban pencemar BOD dan TSS terbesar berasal dari segmen 3 (termasuk dalam guna lahan pemukiman dengan kepadatan tinggi dan guna lahan perdagangan). Kata Kunci: Beban Pencemar, Status Mutu Air, Sungai Rengas